BMAL1 ameliorates type 2 diabetes-induced cognitive impairment via AREG upregulation and PI3K/Akt/GSK-3β pathway activation - Jialu Xu; Chunyu Li; Rongping Fan; Jiaxin Yin; Lei Xie; Xuemin Peng; Jing Tao; Weijie Xu; Shujun Zhang; Xiaoli Shi; Kun Dong; Xuefeng Yu; et al. (Cell Communication and Signaling)
Abstract Cognitive impairment is a significant complication of type 2 diabetes mellitus (T2DM). However, the mechanisms underlying the development of cognitive dysfunction in individuals with T2DM remain elusive. Herein, we discussed the role of Bmal1, a core circadian rhythm-regulating gene, in the process of T2DM-associated cognitive dysfunction. We identified a marked decrease in BMAL1 levels in the hippocampus of db/db mice, followed by gain- and loss-of-function studies to explore the impact of BMAL1 on cognitive function. Our findings indicated that BMAL1 downregulation led to cognitive deficits, characterized by tau hyperphosphorylation and accumulated amyloid plaque. Conversely, BMAL1 overexpression mitigated these Alzheimer-like pathologies. Further investigation revealed that BMAL1 directly activated the transcription of Areg, thereby activating the PI3K/Akt/GSK-3β pathway and ameliorating cognitive dysfunction. Moreover, these effects of BMAL1 were attenuated by LY294002, a PI3K inhibitor. Collectively, these results underscore the significant role of BMAL1 in T2DM-associated cognitive impairment, proposing a novel intervention strategy for individuals exposed to risk factors of T2DM.